An Analysis of Problem Based Learning Strategy In Fostering Students’ Speaking Skill At The Second Semester Of Cokroaminoto Palopo University - Amaliah Rhamadhani; Rusdiana Junaid; Hafirah Patang; Andrika Romi Putra (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
In fostering students’ speaking skills, it is necessary to apply learning strategies that are consistent and in line with developing educational patterns. Problem Based Learning (PBL) is one option for fostering students’ speaking skills because it allows students to think critically about the problems raised in their learning and contributes to their goals in choosing an English major. This research aims to analyze the process of implementing the PBL strategy in fostering students’ speaking skills in class. This research is a qualitative quantitative study conducted at Cokroaminoto Palopo University with a focus on students’ speaking skills. The research was conducted in May–June 2024. This research provides valuable insights and recommendations for optimizing the use of PBL strategies in developing students’ speaking skills. Based on data analysis and interpretation, it is found that the implementation of PBL at the second semester students’ fulfilled four of the five characteristics of PBL proposed by Arends’. They are (1)The problems posed are real-world problems so that students’ can ask questions related to the problem and find various solutions to solve the problem; (2)The learning carried out by students’ is authentic inquiry and in accordance with scientific strategies; (3)The resulting product can be in the form of real work or a demonstration of the problem being solved for publication by students’; (4)Students’ work together and motivate each other regarding the problems they are solving so that they can develop students’ social skill.